Traslatio: study and dissemination of maritime heritage - Oscar Fuertes Dopico; Iago Fernandez Penedo; Carmen Fabregat-Nodar (ESTOA: Revista de la Facultad de Arquitectura y Urbanismo de la Universidad de Cuenca)
The Traslatio project develops research on the southern estuary of Muros-Noia and the northern estuary of Arousa in Galicia, Spain. The aim is to enhance the maritime architectural heritage of both estuaries through the systematic study of buildings associated with small-scale traditional maritime industries, such as salting factories, canneries, traditional shipyards, shellfish farms, whaling factories and ancillary buildings. Following the inventory of the constructions, participatory and dissemination activities are developed with the objective of disseminating knowledge to visitors and pilgrims who travel the sea routes to Santiago de Compostela, engaging with local population and fostering intergenerational dialogue and the transmission of this heritage that represents the identity of the Galician coast.